THE ROLE AND PLACE OF MILITIA IN THE MILITARY-POLITICAL ACTIVITY OF THE FIRST IMAM GAZIMUKHAMMAD (1828-1832) - Dadaev, U U (History, Archeology and Ethnography of the Caucasus, 2015)
The article deals with the appearance and functioning of militia troops under the first Imam Gazimuhammad’s rule. The author presents the documents and eyewitness accounts of the events which showthe time of origin and place of functioning of the militia troops by the Imam. The militia troops are considered to functionwithin the period of 1828–1832. The analysis of Gasanilav Gimrinsky’s well-known work enables to assume that the militia troops first appeared under Imam Gazimuhammad. On a voluntary basisGazimuhammadon a mass scale collected the troops from various areas and societies in one particular place.Any resident who was able and willing could take part in the troops.However, at the days of Gazimuhammad the militia was not a strong, unified and developed military formation. It was the talented military leader and reformer Imam Shamil who was to accomplish it.